The established and emerging roles of astrocytes and microglia in amyotrophic lateral sclerosis and frontotemporal dementia - Radford, Rowan A.; Morsch, Marco; Rayner, Stephanie L.; Cole, Nicholas J.; Pountney, Dean L.; Chung, Roger S. (Frontiers in Cellular Neuroscience, 2015)
Amyotrophic lateral sclerosis (ALS) and Frontotemporal Dementia (FTD) are two progressive, fatal neurodegenerative syndromes with considerable clinical, genetic and pathological overlap. Clinical symptoms of FTD can be seen in ALS patients and vice versa, recent genetic discoveries conclusive link the two diseases, and several common molecular players have been identified (TDP-43, FUS, C9ORF72).The definitive aetiologies of ALS and FTD are currently unknown and both disorders lack a cure. Glia, specifically astrocytes and microglia are heavily implicated in the onset and progression of neurodegeneration witnessed in ALS and FTD. In this review, we summarise the current understanding of the role of microglia and astrocytes involved in ALS and FTD, highlighting their recent implications in neuroinflammation, alterations in waste clearance involving phagocytosis and the newly described glymphatic system, and vascular abnormalities. Elucidating the precise mechanisms of how astrocytes and microglia are involved in ALS and FTD will be crucial in characterising these two disorders and may represent more effective interventions for disease progression and treatment options in the future.